Communication Skills: Syarat Esensial Sukses di Era Informasi? - Muhammad Ainul Yaqin; Muhammad Fariz Nabil Akmal; Nashrul Amin (Literaksi: Jurnal Manajemen Pendidikan, 2023)
The purpose of this research activity is to enable people to reach their maximum potential in a person by expanding their knowledge and skills. This writing uses a descriptive qualitative method by taking notes because the source of the data was obtained by listening to oral narratives.  To achieve success in life, there are many personal development skills that can be trained, such as communication skills.  Communication is very important in the fabric of life, and effective self-development is essential for success. It can happen if we have specific goals, strategies, and tips to help us achieve the end goal.